The impact of donor age and sex on the nucleated cell count and CD34 count in healthy bone marrow donors. (12th March 2015) - Unal Ince, Elif; Ileri, Talia; Dogu, Figen; Ates, Can; Cakmakli, Hasan; Dalva, Klara; Ikinciogullari, Aydan; Uysal, Zumrut; Ertem, Mehmet
Abstract BM remains an important source of stem cells. The BM characteristics change with age but the estimation of CD34 calculation of one CD34+ cell per 100 nucleated cells is used for all donors including pediatric donors in the operating room before getting the actual CD34 count. In order to see whether this formula is applicable for pediatric donors, we designed a retrospective study to see the affect of the age and sex on the BM NCC, CD34 count, and CD34/NCC ratios. Ninety‐eight BM collections from 91 related donors were evaluated retrospectively (median age: nine yr [1.5–54 yr]; M/F: 41/50). A significant negative correlation was found between the donor age and NCC (r = −0.229, p < 0.05), CD34 count (r = −0.563, p < 0.01), and CD34/NCC (r = −0.664, p < 0.01). The negative correlation for CD34 count and CD34/NCC persisted in female and male donor groups. When donors younger than 16 yr of age were compared with the older donor group, the median NCC, median CD34 count, and CD34/NCC were significantly lower in the older group (p < 0.01). Age and sex have to be taken into consideration to avoid unnecessary high‐volume collections and increased operating room time in the younger donors.